An ontology-based coordination and integration of multi-channel online communication. (2017) - Akbar, Zaenal; Fensel, Anna; Fensel, Dieter
While multiple online communication channels have been available on the internet, coordination and integration of those channels have been challenging owing to the inter-operability limitation. Every channel has unique characteristics, and there is no standard format to interchange knowledge among them. In this paper, we propose an ontology-based model to represent communication activities on multiple channels uniformly, in a way that content publication to multiple channels can be coordinated and the received engagements from multiple channels can be integrated. We show how to apply the model to analyse multi-channel publications on popular social media channels from the tourism industry.